Methods for prophylaxis and treatment of subcutaneous cerebrospinal fluid accumulation in the early postoperative period after surgery of skull base meningiomas - Oblyvach, Andrii A. (Ukrainian Neurosurgical Journal, 2017)
The objective of the study was to investigate the causes of postoperative subcutaneous accumulation of cerebrospinal fluid (CSF), improvement of techniques of surgical wound sealing, and the development of a clear algorithm for therapeutic manipulation aimed at eliminating this complication. Materials and methods. During the period from 2004 to 2016 at the Neurosurgery Department of Hospital 196 patients with skull base meningiomas were treated, of which 207 operations were performed. Eighty-eight (44.6%) patients had anterior meningiomas, 73 patients had medium and 36 patients had posterior fossa meningiomas. The patients’ age ranged from 17 to 74 years (mean age 45 years). There were 107 (54.3%) males and 90 (45.7%) females. In order to seal the dura mater for small defects pericranial flaps and aponeurosis fragments as well as muscle and fat tissue fragments and monocomponent medical cyanoacrylate glues as Sulfakrilat and Epiglue were used. Result. We analyzed the data of 161 observations of postcranial fossa and medium fossa meningiomas. Subaponeurotic CSF accumulation in the early postoperative period was revealed in 32 (19.8%) patients. Thirty-two patients had anterior fossa pseudomeningocele eliminated spontaneously. The inclusion criterion was the presence of subcutaneous CSF accumulation since 2nd day by imaging and palpatory data. The paper analyzed the main causes of subaponeurotic CSF accumulation after surgery. Features of soft tissue flapping, craniotomy, resection and sealing of the dura, suturing the surgical wound were important for its prevention. The paper determines the basic methods for medical and surgical correction of complications following as: a pressure bandage, percutaneous aspiration of cerebrospinal fluid syringe, the use of elastic bandages, hypodermic and lumbar drainage, wound revision and sealing. Conclusion. 1. The main reasons for meningocele in the early postoperative period were increased pressure of cerebrospinal fluid and dura mater defect. 2. Even with careful suturing wounds using known methods for dura mater sealing, in the area of craniotomy subaponeurotic accumulation of fluid can occur, mostly in the frontal area due to the elasticity of soft tissue grafts and lack of muscle layer. 3. Pseudomeningocele in the early postoperative period requires all necessary surgical and medical methods for this complication early removing.